2023
DOI: 10.1265/ehpm.22-00276
|View full text |Cite
|
Sign up to set email alerts
|

<i>ALDH2</i> rs671 variant allele is associated with higher energy intake in middle-aged and elderly Japanese who routinely consume alcohol

Abstract: Background According to recent reports, individuals with reduced aldehyde dehydrogenase activity may require more energy for the detoxification of aldehydes. Aldehyde dehydrogenase 2 (ALDH2), an ALDH isozyme, is responsible for detoxifying acetaldehyde, an intermediate metabolite of ethanol. Because the variant allele of the rs671 polymorphism of ALDH2 results in a substantial reduction in enzymatic activity, carriers of this variant allele may have a higher energy deman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…The study assumes that flushing predicts rs671 based on previous studies showing its high accuracy, 88–94% [ 28 30 ], and an overwhelming association between flushing and rs671 among other gene polymorphisms [ 42 ]. Based on the distribution of rs671 and the frequency of flushers in previous studies in Japan, the rate of flushers was expected to be 46%–51% [ 39 , 43 , 44 ]; however, the proportion in the current study was as high as 55%. We speculate that this was because of false positives, especially in elderly individuals, for the following reason.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The study assumes that flushing predicts rs671 based on previous studies showing its high accuracy, 88–94% [ 28 30 ], and an overwhelming association between flushing and rs671 among other gene polymorphisms [ 42 ]. Based on the distribution of rs671 and the frequency of flushers in previous studies in Japan, the rate of flushers was expected to be 46%–51% [ 39 , 43 , 44 ]; however, the proportion in the current study was as high as 55%. We speculate that this was because of false positives, especially in elderly individuals, for the following reason.…”
Section: Discussionmentioning
confidence: 65%
“…Based on the result of the current study, the effect of rs671 is expected to be greater but not robust enough to be found in GWAS, where adjustment for covariates is limited. Based on previous study findings, rs671 is expected to influence several COVID-19-related traits, such as food preference and underlying metabolic conditions and diseases [ 39 41 ], resulting in the inclusion of various noises.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, other literature also discussed the mechanisms between ALDH2 and cardiometabolic risk factors. Previous studies on ALDH2 rs671 polymorphism and T2DM had provided controversial results ( 25 , 35 , 38 , 40 , 57 , 63 , 67 ). This may be due to the sample size of most ALDH2 studies being relatively small (28 included studies of our study had participants less than, 1000), and ALDH2 was interfered with other confounding factors.…”
Section: Discussionmentioning
confidence: 98%